A Sporadic Case of Darier Disease with Acrokeratosis Verruciformis like Lesions: Treated Effectively with Oral and Topical Retinoid - Dr. Smriti Vyas, Dr. Rahul Kumar Sharma M.D., (International Journal of Innovative Research in Medical Science, 2017)
Darier disease (DD) is a type of autosomal dominant genodermatosis with calcium pump defect. We are reporting a case of Darier disease because of its rarity. A 24 year old man presented with multiple pruritic dark warty lesions over the seborrheic areas since 5 years of age. We treated him with retinoids, with which he had considerable improvement. It is necessary to diagnose this condition early as it can adversely affects the quality of life and can be associated with multiple systemic co-morbidities.